Preparedness of Saudi Arabia to Defend Against Cyber Crimes: An Assessment with Reference to Anti-Cyber Crime Law and GCI Index - Alshammari, Tareq Saeed; Singh, Harman Preet (Archives of Business Research, 2018)
With the increasing popularity of ICT, cyber-crimes have increased rapidly. Countries across the globe have made the necessary interventions to ensure cyber-security. Saudi Arabia has been the worst victim of cyber-crimes in the Gulf region. This article investigates the preparedness of Saudi Arabia to defend itself against cyber-crimes. In order to combat against cyber-crimes, Saudi Arabia formed the anti-cybercrimes law in 2007. Global Cyber-security Index of 2017 has placed Saudi Arabia in the maturing stage behind the leading nations. Anti-cybercrimes law covers essential areas to fight against cyber-crimes and states their punishments. However, it is found to be deficient to protect against identity theft, invasion of privacy, cyber-bullying etc. This research finds Saudi Arabia semi-prepared to defend itself against cyber-crimes. In order to be among the leading nations of cyber-security; Saudi Arabia needs to strengthen its anti-cybercrimes law, cyber-security regulations and national cyber-security authority. It needs to develop cyber-security strategy, standards, metrics and R&D programs. It should promote home-grown cyber-security industry, incentivize cyber-security companies and enter into multi-lateral agreements.